The co-existence of NAFLD and CHB is associated with suboptimal viral and biochemical response to CHB antiviral therapy: a systematic review and meta-analysis - Zeng, Georgia; Holmes, Benjamin R.; Alqahtani, Saleh A.; Gill, Upkar S.; Kennedy, Patrick T. F. (Frontiers in Gastroenterology, 2024)
Background and Aims: Chronic hepatitis B (CHB) and non-alcoholic fatty liver disease (NAFLD) are leading causes of liver-related morbidity and mortality. The interaction between these two disease processes is poorly defined and the impact of NAFLD on HBV-related cirrhosis and HCC remains unclear. The aim of this study was to evaluate the impact of NAFLD on response to antiviral CHB therapy to inform the debate on changing CHB treatment thresholds for these comorbid patients. Methods: Studies with a minimum of 50 adult CHB patients on nucleoside analogue therapy with or without concurrent NAFLD were identified from PubMed/Medline and EMBASE to February 21, 2023. Data extraction from each study included HBeAg and treatment status, diagnostic method of NAFLD, frequency of monitoring intervals, patient age, gender, grade of hepatic steatosis, BMI and metabolic comorbidities. The outcomes of interest, complete virological response (CVR), biochemical response (BR) and HBeAg loss/seroconversion, were recorded at each available monitoring interval. Comparing CHB-NAFLD and CHB-only groups, pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated using random- or fixed-effects models depending on heterogeneity. Results: From a search of 470 citations, we identified 32 potentially relevant papers. Overall, 11 studies, comprising 2580 unique patients, met the inclusion criteria of the meta-analysis. CHB-NAFLD patients exhibited significantly lower rates of CVR compared to CHB-only patients. This was demonstrated by an OR of 0.59 (0.38-0.93, p=0.001, I2=72%) at 12 months, which tapered off to an OR of 0.67 (0.48-0.95, p=0.02) at 60 months. CHB-NAFLD patients also exhibited significantly lower rates of BR compared to CHB-only patients, as demonstrated by ORs of 0.39 (0.24-0.62, p<0.0001, I2=53%) at 12 months and 0.33 (0.17-0.63, p=0.0008) at 24 months. Conclusion: Patients with concurrent CHB and NAFLD experience delayed CVR to antiviral therapy and more persistent biochemical abnormalities in comparison to patients with CHB only. This supports the argument for earlier antiviral therapy in order to avert CHB complications in these multi-morbid patients, as the global disease burden of NAFLD continues to increase.